2018
DOI: 10.3390/polym10080824
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Two Polymer-Based Superplasticizers (Poly-naphthalene Sulfonate, PNS, and Lignosulfonate, LS) on Compressive and Flexural Strength, Freeze-Thaw, and Sulphate Attack Resistance of Lime-Metakaolin Grouts

Abstract: A new range of grouts prepared by air lime and metakaolin (MK) as a pozzolanic admixture has been obtained by using as dispersing agents two polymers, namely poly-naphthalene sulfonate (PNS) and lignosulfonate (LS), with the aim of improving the fluidity of the fresh grouts. Fluidity and setting times of the grouts were assessed. Differences in the molecular architecture and in the anionic charge density explained the different adsorption of the polymers and the different performance. The higher anionic charge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 63 publications
1
16
0
Order By: Relevance
“…It was shown that not all superplasticizers could improve the performance of FA geopolymer concrete: with polycarboxylic-based superplasticizers, no significant difference in the performance of FA geopolymer concrete was observed; however, by adding 2% of naphthalene sulfonate-based superplasticizer (compared to FA), the workability was improved but the compressive strength was not affected. In the present study, a lignosulfonate superplasticizer (Sika, Baar, Switzerland) was used because lignosulfonate and naphthalene sulfonate are considered the most widely used superplasticizers [ 26 ]. The used superplasticizer was a current commercial product in liquid form.…”
Section: Methodsmentioning
confidence: 99%
“…It was shown that not all superplasticizers could improve the performance of FA geopolymer concrete: with polycarboxylic-based superplasticizers, no significant difference in the performance of FA geopolymer concrete was observed; however, by adding 2% of naphthalene sulfonate-based superplasticizer (compared to FA), the workability was improved but the compressive strength was not affected. In the present study, a lignosulfonate superplasticizer (Sika, Baar, Switzerland) was used because lignosulfonate and naphthalene sulfonate are considered the most widely used superplasticizers [ 26 ]. The used superplasticizer was a current commercial product in liquid form.…”
Section: Methodsmentioning
confidence: 99%
“…When using the glass microspheres as a weight-reducing filler in a hydrated lime grout composition, the viscosity of the paste must be high enough to prevent the segregation of solid particles. To provide both an increased viscosity and adequate injectability of the hydrated lime grout, superplasticiser (SP; polymeric admixture) can be incorporated into the grout mixture [ 13 , 14 ]. Subsequently, much lower water content is needed for adequate workability and injectability.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, much lower water content is needed for adequate workability and injectability. Among three SP groups frequently used in the lime-based grouts—poly-naphthalene sulfonates (PNS), lignosulfonates (LS) and polycarboxylate ethers (PCE)—the PCE products seem to be the most efficient solution [ 1 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many research projects on zeta potential measurements have been conducted to investigate the working mechanism of superplasticizers in cement pastes. The zeta potential test allows to quantify the electrostatic repulsion caused by adsorbed superplasticizers (Duran et al, 2018). Generally, a high (negative or positive) zeta potential value indicates high electrostatic repulsion between particles (Duran et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The zeta potential test allows to quantify the electrostatic repulsion caused by adsorbed superplasticizers (Duran et al, 2018). Generally, a high (negative or positive) zeta potential value indicates high electrostatic repulsion between particles (Duran et al, 2018). The physical characteristics and chemical composition of fly ash are very different from those of cement.…”
Section: Introductionmentioning
confidence: 99%